Penyuluhan Pertanian dan Ambiguitas Pembangunan - Denny Riezki Pratama; Brainy Brilliant (Umbara, 2022)
This research discusses agricultural assistance program as a practice in Indonesia’s development discourse. This research aims to investigate the meaning and practice of agricultural assistance in daily local interactions that show the contradictions and ambiguities of Indonesia’s development process. Agricultural assistance provides project opportunities and economic benefits. However, at the same time, it also shows the contradiction of meanings and conflict of interest, in the asymmetrical relations of development. Thus, a local development practice conducted with negotiations, resistances, contradictions, and could leads to manipulatives and corruption emerged.